2012
DOI: 10.1111/j.1469-8137.2012.04358.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular aspects of the antagonistic interaction of smoke‐derived butenolides on the germination process of Grand Rapids lettuce (Lactuca sativa) achenes

Abstract: SummarySmoke-derived compounds provide a strong chemical signal to seeds in the soil seed bank, allowing them to take advantage of the germination niche created by the occurrence of fire. The germination stimulatory activity of smoke can largely be attributed to karrikinolide (KAR 1 ), while a related compound, trimethylbutenolide (TMB), has been shown to have an inhibitory effect on germination. The aim of this study was to characterize the interaction of these potent firegenerated compounds.Dose-response ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 48 publications
(60 reference statements)
3
33
0
Order By: Relevance
“…The different growth responses of okra obtained with KAR 1 and smoke–water application may be explained by these compound(s) having different modes of action, with smoke–water comprising thousands of volatile compounds ( Light et al, 2009). The mode(s) of action by which the various smoke‐derived compounds influence plant growth have not been fully elucidated although gene expression and protein ubiquitination patterns are different with smoke–water and KAR 1 application ( Soós et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The different growth responses of okra obtained with KAR 1 and smoke–water application may be explained by these compound(s) having different modes of action, with smoke–water comprising thousands of volatile compounds ( Light et al, 2009). The mode(s) of action by which the various smoke‐derived compounds influence plant growth have not been fully elucidated although gene expression and protein ubiquitination patterns are different with smoke–water and KAR 1 application ( Soós et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…This improved growth may have been caused by B. licheniformis favorably influencing the hormone profile although this interaction requires further investigation. Although not elucidated, the mechanisms of action of TMB are different to those of KAR 1 with TMB reducing the stimulatory effect of KAR 1 in a concentration‐dependent manner but not competing for the same binding sites ( Soós et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Karrikinolide is active at concentrations as low as 10 ‐9 M (Soós et al . ) and it is suggested to act via gibberellin (GA) signalling in Arabidopsis , either by inducing GA biosynthesis (Nelson et al . ) or by affecting the signalling pathway (Janssen & Snowden ; Meng et al .…”
Section: Introductionmentioning
confidence: 99%
“…germinated readily in the dark, data not shown). In another study, it was noted that the inhibitory effect of 2 could be alleviated following rinsing/leaching of the compound, while the promotory effect of 1 was only reversible following leaching within the first 2 h of treatment (Soós et al, 2012). A preliminary test indicated that rinsing the lettuce seeds with distilled water after 24 h treatment with 1 mM 6 or 7 in the dark at 25 • C allowed for normal seedling development when transferred to the light (data not shown).…”
Section: Evaluation Of Germination Activitymentioning
confidence: 86%
“…2; Light et al, 2010). This inhibitor (2) was shown to be active at 10 and 100 M, and application together with 0.1 M KAR 1 (1) suppressed germination of 'Grand Rapids' lettuce seeds Although there has been an intensive effort toward elucidation of the mode of action of KAR 1 (1) and structurally-related karrikins (Bythell-Douglas et al, 2013;Flematti et al, 2010;Kagiyama et al, 2013;Nelson et al, 2009Nelson et al, , 2010Nelson et al, , 2011Scaffidi et al, 2011Scaffidi et al, , 2012Soós et al, 2010;Waters et al, 2012;Waters and Smith, 2013), relatively little research has been carried out investigating the action of the germination inhibitor 2, with the exception of one recent study (Soós et al, 2012), which found that these two compounds are not direct competitors. Thus, in order to further study the action of the naturally occurring inhibitor 2, we initiated a structure-activity relationship study of synthetic analogs to determine the influence of substituents with differentiated electronic and steric properties to the inhibitory activity.…”
Section: Introductionmentioning
confidence: 98%